2015
DOI: 10.3390/f6030769
|View full text |Cite
|
Sign up to set email alerts
|

Organic Carbon Accumulation in Topsoil Following Afforestation with Willow: Emphasis on Leaf Litter Decomposition and Soil Organic Matter Quality

Abstract: Short-rotation intensive cultures (SRICs) of willows can potentially sequester carbon (C) in soil. However, there is limited information regarding the factors governing soil organic C (Corg) accumulation following afforestation. The objectives of this study were to: (i) determine whether willow leads to Corg accumulation in the topsoil (0-10 cm) two to six years after establishment in five SRICs located along a large climatic/productivity gradient in southern Quebec, and (ii) assess the influence of leaf litte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…The quality, function, and biochemical stability of SOC depend on the relative abundance of soil LC versus RC functional groups (Beer et al 2008). As the soil organic matter (SOM) under different vegetation types from contrasting land-use practices decomposes, the chemical composition of SOC changes (La eur et al 2015;Deng et al 2019). Advanced analytical techniques such as Fourier Transform Infrared (FTIR) spectroscopy can reveal the biochemical characteristics at molecular-scale and relative abundance of C compounds (i.e., polysaccharides, phenolic, amides, aromatic, carboxylic) via the ratios of RC and LC fractions (Calderón et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The quality, function, and biochemical stability of SOC depend on the relative abundance of soil LC versus RC functional groups (Beer et al 2008). As the soil organic matter (SOM) under different vegetation types from contrasting land-use practices decomposes, the chemical composition of SOC changes (La eur et al 2015;Deng et al 2019). Advanced analytical techniques such as Fourier Transform Infrared (FTIR) spectroscopy can reveal the biochemical characteristics at molecular-scale and relative abundance of C compounds (i.e., polysaccharides, phenolic, amides, aromatic, carboxylic) via the ratios of RC and LC fractions (Calderón et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Grassland afforestation is an artificial and direct change in vegetation that alters both the above- and underground ecosystems, including abiotic changes (Li et al, 2016; Peng et al, 2014; Khamzina, Lamers & Martius, 2016; Lafleur et al, 2015), biotic changes (Ma et al, 2013; Márquez et al, 2015; Pedley et al, 2014; Gunina et al, 2017; Šnajdr et al, 2013; Xiao et al, 2017), and ecological function changes (Lu et al, 2017; Ren et al, 2016; Cibils et al, 2015). Land use is a significant determinant of runoff and soil redistribution processes (Arnáez et al, 2015), and soil microbial species responses may be sensitive to compositional changes in both species and ecological functions (Xiao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies on SRW suggested con icting results regarding SOC accumulation compared to other land-use practices. For example, the topsoil SOC increased under SRW plantation, on former agricultural land compared to conventional AC(Dimitriou et al 2012), adjoining agricultural elds(La eur et al 2015)…”
mentioning
confidence: 99%